Gaining Political Legitimacy through Social Dialogue: The Interest Representation of European Employers’ Organizations - Gooberman, Leon; Hauptmeier, Marco (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2024)
This article examines the interest representation of European Employers’ Organizations (EEOs) in the European Union (EU). Previous literature in employment relations focused on employer activity in social dialogue, while literature in political science focused on political representation and how business associations lobby EU political institutions. Going beyond this dualism in the literature, this article suggests that gaining a full understanding of the interest representation of European Employers Organizations requires analyzing interactions between the political and social dialogue arenas. We argue that EEOs gain legitimacy through participating in social dialogue to facilitate their primary focus of political interest representation. Strategic and institutional perspectives on legitimacy provide insights into how EEOs respond to challenges and manage their environment within the EU to pursue their interests.